Efektifitas Pijat Woolwich Terhadap Produksi Asi di Bidan Praktek Mesra Wilayah Puskesmas Pintu Padang Kecamatan Batang Angkola Kabupaten Tapanuli Selatan - Irwan Batubara; Sri Juwarni; Meidiawaty; Anita Agustini Batubara (Jurnal Anestesi, 2024)
In order to reduce child morbidity and mortality, the United Nations Children's Fun (UNICEF) and the World Health Organization (WHO) recommend that children should only be given breast milk for at least six months (Infodatin, 2020). Adequacy of breast milk prevents hunger and malnutrition, reduces infant mortality, improves mental and cognitive development of infants. Woolwich massage increases the hormones prolactin and oxytocin which play a role in stimulating the release of milk in mothers after giving birth. Woolwich massage. carried out in the area of the lactiferous sinuses exactly 1-1.5 cm above the areola mamae, with the aim of removing the milk that is in the lactiferous sinuses. The purpose of this study is to analyze the effect of the woolwich massage method on increasing breast milk production for the adequacy of babies in postpartum mothers in the Pintu Padang Health Center area, South Tapanuli Regency. Quasiexperimental study Woolwich massage on mammary glands. Population Mother post partum 1-4 days. The total population sample is 20 respondents. Research time June to November 2022. The results of the Pearson correlation test of 0.751 with a significance level (p) of 0.058 indicate a strong correlation and a positive direction where the woolwich massage facilitates the release of breast milk in meeting the needs of the baby. Midwives are motivated to do woolwich massage in the mammary area after assisting in childbirth.